Nasal Mucoadhesive In-Situ Gel of Granisetron Hydrochloride using Natural Polymers - Kailas K Mali, Shashikant C Dhawale, Remeth J Dias, Vijay D Havaldar, Vishwajeet S Ghorpade, Nitin H Salunkhe (Journal of Applied Pharmaceutical Science, 2015)
The prolonged residence of drug formulation in the nasal cavity is of utmost importance for intranasal delivery of drug. Present investigation was aimed to develop a mucoadhesive in situ gel of Granisetron hydrochloride (GH) with reduced nasal mucocilliary clearance in order to improve the bioavailability of the antiemetic drug, granisetron hydrochloride. The in situ gelation upon contact with nasal mucosa was conferred via the use of the thermogelling Pluronic flake 127 (PF 127). Moringa gum (MG), carboxymethyl tamarind gum (CMTG) and sodium alginate (SA) was used to modulate mucoadhesion whereas drug release of optimized formulation was modified by 0.3% polyethylene glycol 6000 (PEG 6000). Results revealed that as the concentration of mucoadhesive polymer increased the mucoadhesive strength increased and gelation temperature decreased significantly. Preformulation studies showed that addition of GH in 18% PF 127 gels modulated gelation temperature significantly while mucoadhesive polymers alters mucoadhesion. Formulation F6, F11 and F15 showed more than 80% of drug diffusion at 240 min. Gelation temperature and mucoadhesive strength of all three formulations were found in the range of 30-31 ï‚°C and 963.66±9.60 to 991.33±10.26 dyne/cm2 respectively. Formulation F11 showed optimum results and further histopathological evaluation reveled formulation is safe for use. Addition of PEG 6000 increased drug diffusion in formulation F11 with flux 0.034 mg.cm2/min. This study concluded the potential use of CMTG as mucoadhesive in situ nasal gel in terms of ease of administration, accuracy of dosing, prolonged nasal residence and improved nasal bioavailability.
Keywords: Carboxymethyl tamarind gum, Granisetron HCl, Mucoadhesive, Moringa gum, Nasal in situ gel.